Edukasi Infeksi Menular Seksual Pada Pedagang di Daerah Wisata - Musyarrafah Musyarrafah; Halia Wanadiatri; Aena Mardiah; Rusmiatik Rusmiatik (Universitas Mataram, 2019)
Sexually transmitted infections (STIs) or venereal diseases are one of the reproductive health issues that are currently in the top 10 infectious diseases in several developing countries, such as in Indonesia. This type of infectious disease has a high risk in tourist areas due to its strong tendency for spreading the disease. This study aims to enhance the awareness and the understanding of the STI of traders in the tourist area, Nipah Beach, North Lombok Regency. The methods that are used counseling and education, and discussion. The result of the study shows after the implementation of this activity, the traders have a better understanding of STIs and they can apply reproductive health to individuals, families, and the tourist environment